Coupled-Mode Theory for Semiconductor Nanowires - Buschlinger, Robert; Lorke, Michael; Peschel, Ulf (Physical Review Applied, 2017)
We present a model to describe the spatiotemporal evolution of guided modes in semiconductor nanowires based on a coupled-mode formalism. Light-matter interaction is modeled based on semiconductor Bloch equations, including many-particle effects in the screened Hartree-Fock approximation. Appropriate boundary conditions are used to incorporate reflections at waveguide end facets, thus allowing for the simulation of nanowire lasing. We compute the emission characteristics and temporal dynamics of CdS and ZnO nanowire lasers and compare our results both to finite-difference time-domain simulations and to experimental data. Finally, we explore the dependence of the lasing emission on the nanowire cavity and on the material relaxation time.
CRIS-Team Scopus Importer:2023-04-20